Obesity and the Risk of Incident Chronic Opioid Use in Rheumatoid Arthritis. Issue 10 (31st August 2021) - Baker, Joshua F.; Stokes, Andrew; Pedro, Sofia; Mikuls, Ted R.; George, Michael; England, Bryant R.; Sayles, Harlan; Wolfe, Fred; Michaud, Kaleb
Abstract : Objective: The present study was undertaken to evaluate whether the rate of incident chronic opioid use is higher in obese patients with rheumatoid arthritis (RA). Methods: Participants with RA in the FORWARD databank were asked about their use of weak and strong opioid medications on semiannual surveys. Incident chronic opioid use was defined as new reported use extending over 2 contiguous surveys (~7–12 months). Cox proportional hazards models were used to evaluate associations between body mass index (BMI) at enrollment and incident chronic opioid use (overall use and strong opioid use). Models adjusted for demographics, smoking, disease duration, RA treatments, household income, and education level. The predicted 5‐year cumulative incidence was calculated from Cox models. Results: Among 19, 794 participants, 2, 802 experienced an incident episode of chronic opioid use over 93, 254 person‐years of follow‐up. Higher BMI was associated with higher risk of chronic opioid use. Severe obesity (BMI >35 kg/m 2 ) was associated with a higher risk of overall use (adjusted hazard ratio [HRadj ] 1.74 [95% confidence interval (95% CI) 1.72–2.04], P < 0.0001) and strong opioid use (HRadj 2.11 [95% CI 1.64–2.71], P < 0.001) compared to normal BMI. This association was partially explained by greater comorbidity, pain, and disability in obese groups. The attributable risk for obesity was 15% of overall opioid use and 24% of strong opioid use. Conclusion: Obesity is associated with a substantially higher risk of incident chronic opioid use. Approximately 1 in 4 cases of incident use of strong opioids may be attributable to obesity, suggesting a major public health impact. Interventions to prevent or reduce obesity could have an important impact on the use of opioids.